EFEKTIFITAS PENDIDIKAN KESEHATAN INDIVIDUAL DENGAN MENGGUNAKAN MEDIA FLIPCHART DAN FOOD MODEL TERHADAP KEPATUHAN PASIEN DIABETES MELLITUS TIPE 2 DALAM MELAKSANAKAN DIET DAN OLAHRAGA - Ikhtiarillah " Adintifa; Gamya Tri Utami; Erwin " " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract Health education is a form of intervention or effort devoted to the behavior that such behavior conducive to health. Health education can be given by media that attract people with diabetes mellitus, like flipchart and food models. Health education is to increase compliance behavior of patients with type 2 diabetes mellitus in implementing diet and physical exercise. This research aims to find out the effectiveness of individual health education to compliance of patients with type 2 diabetes mellitus in implementing diet and physical exercise. The research method was quasy experimental with pre test and post test with control group design. The sampling technique used purposive sampling with 34 respondents, it divided into two groups, experiment group and control group. Instruments for this research used questionnaires that have been tested for validity (0.488-0.756) and reliability (0.922). Analysis used univariate analysis to find out the distribution of compliance and bivariate analysis using t dependent and independent t test. The result showed the influence of individual health education with flipchart and food models to compliance of patients with type 2 diabetes mellitus in implementing diet and physical exercise with p value (0.000) < α (0.05). Based on the result, the author recommend for health workers were give health education by using media flipchart and food models to improve the compliance of patients with type 2 diabetes mellitus in implementing diet and exercise. Keyword: Compliance, flipchart, food model, health education, type 2 diabetesmellitus